2014
DOI: 10.1016/j.renene.2013.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear aeroelasticity: An approach to compute the response of three-blade large-scale horizontal-axis wind turbines

Abstract: In this work, we present an aeroelastic model intended for three-blade large-scale horizontal-axis wind turbines. This model results from the coupling of an existing aerodynamic model and a structural model based on a segregated formulation derived in an index-based notation that enables combining very different descriptions such as rigid-body dynamics, assumed-modes techniques and finite element methods. The developed structural model comprises a supporting tower, a nacelle, which contains the electrical gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 60 publications
2
18
0
Order By: Relevance
“…Examples of FSI using vortex‐based methods are found in Kim et al ,. Riziotis, Manolas and Voutsinas, Gebhardt and Roccia, Branlard et al ,. Hauptmann et al .…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Examples of FSI using vortex‐based methods are found in Kim et al ,. Riziotis, Manolas and Voutsinas, Gebhardt and Roccia, Branlard et al ,. Hauptmann et al .…”
Section: Introductionmentioning
confidence: 95%
“…combined a free‐wake vortex particle model called GENUVP, in which rotor blades are modeled as thin lifting surfaces, with a beam model based on Hodges as well. Gebhardt and Roccia combined an unsteady vortex lattice method with a structural model based on a segregated formulation. Branlard et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prowell et al simulated the dynamic response of a 5‐MW wind turbine subjected to an earthquake via FAST and suggested that the bending moment at tower base in response to an earthquake in a high‐intensity region was the internal control force in wind turbine tower design. Although multisystem dynamics and modal analysis have been combined to analyze the dynamic response of wind turbines, an approach, which has developed significantly in recent years, such a method is unable to simulate the nonlinear behavior of the tower structure material and cannot precisely simulate wind turbine failure and collapse under extreme loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Although multisystem dynamics and modal analysis have been combined to analyze the dynamic response of wind turbines, an approach, which has developed significantly in recent years, [7][8][9][10][11][12][13] such a method is unable to simulate the nonlinear behavior of the tower structure material and cannot precisely simulate wind turbine failure and collapse under extreme loading conditions.…”
mentioning
confidence: 99%